Body-Shaming as Humor Superiority: A Discourse Analysis of Sekawan Limo (2024) - Falesha Libertalea Taufik; Ranang Agung Sugihartono (INJECT (Interdisciplinary Journal of Communication), 2025)
This study analyzes the phenomenon of normalizing body-shaming humor in the Indonesian comedy film Sekawan Limo (2024), using a qualitative narrative study approach, focusing on discourse analysis of dialogue and interactions between characters to reveal how body-shaming-based humor is constructed. Data were collected from dialogue in the film scenes and analyzed using a critical paradigm aimed at sparking social change. The results show that body-shaming is consistently portrayed as a joke, with the character Juna being the primary target. These jokes are found in various forms, such as comparing Juna to ugly mythological figures, direct comments that demean his physical appearance, and nicknames that associate his character with his physique. The use of humor aligns with the theory of superiority humor, where laughter arises from feelings of superiority or satisfaction derived from demeaning others. This study argues that the normalization of body-shaming in the film functions as a degradation ceremony. The sociological process reduces Juna's identity to a mere object of laughter. This process also contributes to cultural hegemony by reinforcing the view that non-ideal bodies are acceptable objects of ridicule, which ultimately influences how viewers view ideal body standards. Films serve not only as entertainment but also as a reflection and formation of social values. Critical reflection on the role of media in reproducing social norms and the ethics of producing more inclusive entertainment content is necessary.